Carbon Deposition Studies in the Steam Reforming of Methane Using an Equilibrated Mixture - Beata Stasińska; Andrzej Gołębiowski; Kazimierz Stołecki; Tadeusz Borowiecki (Adsorption Science & Technology)
Nickel catalysts are commonly used in many industrial processes including the hydrogenation, hydrotreatment, hydrogenolysis, methanation and steam reforming of hydrocarbons. One of the important problems associated with these processes is the coking of such catalysts and in the present paper a new technique for measuring the coking rate in the steam reforming of hydrocarbons is presented. The methodology employed eliminates objections raised concerning gravimetric methods which are most frequently employed in the study of the rate of coking of catalysts. Qualitative agreement between the results obtained using both methods was demonstrated for catalysts differing both in composition and texture. The new method allows a better characterization of the resistance towards coking of nickel on various supports and in the presence of various promoters.